Analysis of Motivational Elements of Social Games: A Puzzle Match 3-Games Study Case. (30th December 2012) - Omori, Marcel Toshio; Felinto, Alan Salvany
Abstract : The main motivational elements of the social network sites and the social network games will be shown according to studies already existent in the literature, highlighting the elements which motivate the players the most to play social Match 3-type games. Seven games have been analyzed: Diamond Dash, Collapse! Blast, Mystic Ice Blast, Bricks Breaking, Plock, Gem Clix, and Blast! . The results showed that asynchronous time, activities publishing, rewarding system, competition, and social status are the elements which motivate and stimulate the most the players to play.